Socio-demographic characteristics associated with health related quality of life among hypertensive patients in Federal Medical Centre Owerri, Imo State Nigeria - Irene, Ugwu Chijioke; Ismail, Suriani; Abdul Manaf, Rosliza; Uchegbu, U.N. (Community Health Society Malaysia, 2018)
Background: Hypertension is one of the biggest threats not only to developed countries but the middle and low income countries such as Nigeria, are equally affected. To react to the growing prevalence of hypertension in Nigeria, it is necessary to have an understanding about the quality of life (QOL) among hypertensive individuals and its related factors. This study aimed to assess the health related quality of life (HRQOL) among hypertensive patients and it association with socio-demographic characteristics. Materials and Method: A cross sectional study was conducted in 2017. A total of 630 hypertensive patients in Federal Medical Centre (FMC) aged above 20years were recruited. Data was obtained using a pretested structured self-administered questionnaire and analysed using IBM SPSS version 22. Health related quality of life (HRQOL) was defined by four domains using the World Health Organization Quality of Life-Bref (WHOQOL-BREF) instrument measuring the physical, psychological, social and environment. The mean score of items were scaled in a positive direction, higher scores denote higher QOL. Independent t- test and one-way ANOVA was used to determine the association between HRQOL and the socio-demographic characteristics of the respondents. Result: In this study HRQOL among hypertensive patients was found moderate in all domains, with highest mean satisfaction found on social and environmental domains. This study also shown that HRQOL was significantly lower among hypertensive patients with lower education (p< 0.001), marital status (p<0.001) lower monthly income (p<0.001). Conclusion: This study revealed that HRQOL of hypertensive patients in FMC, Owerri Imo State, Nigeria to be moderate in all domains. Education level, marital status and income were important independent factors affecting all domains in the patients’ HRQOL.